Investigation of Ecorecreational Attitudes of Faculty of Sport Sciences Students - YILMAZ, Gülsüm; GENÇ, Neşe; TAŞTAN, Zarife (International Journal of Holistic Health, Sports and Recreation, 2023)
The aim of this study is to examine the attitudes of sports sciences faculty students towards echo-recreation according to the variables of gender, time to participate in eco-recreational activities, daily leisure time and frequency of going to natural areas. The study group of the research consists of a total of 268 university students, 101 of whom are female and 167 are male, selected by convenience sampling method. The data of the study were collected with the personal information form and the Scale of Attitude Towards Eco-recreation. When the descriptive statistics of the data, independent samples T-test and one-way analysis of variance anova results were examined, it was determined that there was no significant difference in the attitudes of sports sciences faculty students towards echo recreation according to gender, the department they studied, daily leisure time and frequency of going to natural areas. In addition, it was concluded that there is a significant difference in the level of university students’ attitudes towards eco-recreation according to the variable of participation in eco-recreational activities. According to the duration of participation in eco-recreational activities, it was determined that the attitude averages of the students who participated for 5 years or more differed significantly compared to the averages of the students whose participation period was less than 1 year. As a result, it is seen that personal consumption has gradually increased with the economic developments and the increase in the population today. Considering the current ecology and environmental protection problems, it is important to develop positive attitudes towards eco-recreation in terms of protecting natural resources.